Effects of Environmental Pollutants on Tryptophan Metabolism - Hongyang Hu; Xiaoxun Lu; Miaoliang Wu; Zhi Bai; Xiaoshan Liu (Toxics)
Tryptophan (Trp) is an important essential amino acid that plays a variety of physiological functions in the human body, including being a precursor of neurotransmitter and participating in immune regulation. Currently, more and more studies show that some pollutants in the environment can affect the metabolism of Trp and consequently affect human health. The present paper offers a comprehensive overview of prior research investigating the impact of environmental pollutants, including inorganic and organic contaminants, microplastics, and nanoplastics on the nervous system, immune system, digestive system, and maternal–fetal pregnancy, revealing their detrimental effects on Trp metabolism and human well-being.